Targeting glucose control in preterm infants: pilot studies of continuous glucose monitoring. Issue 4 (19th July 2019) - Thomson, Lynn; Elleri, Daniela; Bond, Simon; Howlett, James; Dunger, David B; Beardsall, Kathryn
Abstract : Objective: Hyperglycaemia is common in very preterm infants and is associated with adverse outcomes. Preventing hyperglycaemia without increasing the risk of hypoglycaemia is difficult. Real time tracking with continuous glucose monitors (CGM) may improve glucose control. We assessed the feasibility and safety of CGM to target glucose control in preterm infants, to inform a randomised controlled trial (RCT). Design: We performed a single centre study in very preterm infants during the first week of life. Accuracy was assessed by comparison of CGM with blood glucose levels (n=20 infants). In a separate pilot study of efficacy (n=20), real-time CGM combined with a paper guideline to target glucose control (2.6–10 mmol/L) was compared with standard neonatal care (masked CGM). Questionnaires were used to assess staff acceptability. Results: No concerns were raised about infection or skin integrity at sensor site. The sensor performed well compared with point-of-care blood glucose measurements, mean bias of −0.27 (95% CI −0.35 to −0.19). Per cent time in target range (sensor glucose 2.6–10 mmol/L) was greater with CGM than POC (77% vs 59%, respectively) and per cent time sensor glucose >10 mmol/L was less with CGM than POC (24% vs 40%, respectively). The CGM also detected clinically unsuspected episodes of hypoglycaemia. Staff reported that the use of the CGM positively improved clinical care. Conclusions: This study suggests that CGM has sufficient accuracy and utility in preterm infants to warrant formal testing in a RCT.